Evaluation and integration of disparate classification systems for clefts of the lip - Wang, Kathie H.; Heike, Carrie L.; Clarkson, Melissa D.; Mejino, Jose L. V.; Brinkley, James F.; Tse, Raymond W.; Birgfeld, Craig B.; Fitzsimons, David A.; Cox, Timothy C. (Frontiers in Physiology, 2014)
Orofacial clefting is a common birth defect with wide phenotypic variability. Many systems have been developed to classify cleft patterns to facilitate diagnosis, management, surgical treatment, and research. In this review, we examine the rationale for different existing classification schemes and determine their inter-relationships, as well as strengths and deficiencies for subclassification of clefts of the lip. The various systems differ in how they describe and define attributes of cleft lip phenotypes. Application and analysis of the cleft lip classifications reveal discrepancies that may result in errors when comparing studies that use different systems. These inconsistencies in terminology, variable levels of subclassification, and ambiguity in some descriptions may confound analyses and impede further research aimed at understanding the genetics and etiology of clefts, development of effective treatment options for patients, as well as cross-institutional comparisons of outcome measures. Identification and reconciliation of discrepancies among existing systems is the first step towards creating a common standard to allow for a more explicit interpretation that will ultimately lead to a better understanding of the causes and manifestations of phenotypic variations in clefting.